Services For Population Administration In The City Of Jayapura - Renyaan, Dorthea (Journal of Research and Development on Public Policy, 2023)
Improving the quality of public services is necessary in order to reduce policy implementation failures caused by misread communication variables. The communication strategy is used to ensure that public services are delivered in a coordinated manner. The goal of this research was to determine the communication strategy for enhancing the quality of public services on the performance of Civil Registry and Population Service staff in Jayapura. This essay employs a non-interactive qualitative technique with descriptive analysis. While the data collection technique employed is literature study, which includes books, papers, internet news, and authoritative organisation websites. The strategic communication initiatives to improve public services headed by the Jayapura City Population and Civil Registry Service are an important conclusion from this research.